Clinical signature of exosomal tetraspanin proteins in cancer - Asmit Das; Priyanka Saha; Ketki Kalele; Swarup Sonar (Wiley, 2024)
Abstract Exosomes are nano‐scale vesicles involved in intercellular communication and have a significant role in cancer progression. Tetraspanins, are transmembrane proteins enriched in exosomes. These proteins have significant role in exosome biogenesis, cargo sorting,and target‐cell interactions, influencing tumor development and therapeutic response. Exosomal tetraspanins, including CD9, CD63, CD81, and Tspan8, contribute to tumor cell proliferation, angiogenesis, extracellular matrix remodelling, immune evasion, and promote metastasis. Their ability to prepare distant organ sites for colonization highlights their role in establishing the premetastatic niche. Expression profiling of exosomal tetraspanin proteins in cancer become a promising diagnostic and prognostic biomarker. Exosomal tetraspanin proteins also be an effective therapeutic target in cancer.This article highlighted impactful role ofexosomal tetraspanin Proteins in Cancer.